BIM in construction projects - Tibaut, Andrej; Žalig, Vito; Časar, Rok; Jakoša, Denis (Anali PAZU, 2022)
The paper describes experiences with research, implementation and analysis of BIM applied in a real infrastructure construction project. The two construction projects “Underpass Grlava” and “Underpass Ljutomer” were carried out in frame of the project Electrification and reconstruction of railway line Pragersko - Hodoš. The result of our research is the 3D- and 4D-model, which the construction company used to monitor last construction phases. The research obtained empirical data during scheduled construction activities and proposes guidelines for efficient use of 4D-model in the building process. Our results can serve as practical recommendations to the construction sector for the tasks of monitoring performance of scheduled activities with the aim to control the cost of construction process.
Keywords: BIM; 3D-model; 4D-model; construction process monitoring